German Colonists on River Milky Waters of Taurida Province in First Third of 19th Century - L. G. Stepanova (Научный диалог, 2022)
The information from the materials of the General Land Survey of the Russian Empire in the first third of the 19th century about the German colonies based on the territory of the Melitopol district of the Tauride province is analyzed in the article. The relevance of the study is due to the great interest in the resettlement policy pursued by the Russian Empire in this region at the end of the 18th — the first third of the 19th centuries, as well as in the processes of settlement and development of new territories and the participation of foreign colonists in them. The novelty of the study lies in the involvement of previously unused “Economic notes on the plans of the General survey, field notes of land surveyors and controversial cases” as sources on the history of German colonists. Based on them, the author studies the features of the economic structure of the settlements of German colonists, the structure of their land. Particular attention is paid to the dispute between the Mennonites and the Dukhobors about the boundaries of possessions, during which the true location of the Molochnaya River bed was clarified. The consideration of the case shows that disputes over the boundaries of land plots were of a fundamental nature and reached the highest authorities. Until the 1830s, there were still unresolved issues related to land management and surveying of the German-speaking colonies.